Discovery of novel serum peptide biomarkers for cholangiocarcinoma recurrence through MALDI-TOF MS and LC–MS/MS peptidome analysis - Vasin Thanasukarn; Piya Prajumwongs; Nattha Muangritdech; Watcharin Loilome; Nisana Namwat; Poramate Klanrit; Arporn Wangwiwatsin; Sawanya Charoenlappanit; Janthima Jaresitthikunchai; Sittiruk Roytrakul; Attapol Titapun (Scientific Reports)
Abstract Cholangiocarcinoma (CCA) is an aggressive cancer originating from bile duct epithelial cells, with a high rate of recurrence following surgical resection. Recurrence is categorized as early linked to aggressive tumor biology than late recurrence. This study aimed to identify novel peptide mass fingerprints (PMFs) and potential biomarker panels in the serum of CCA patients with early and late recurrence using mass spectrometry. Serum samples of 81 CCA patients were analyzed using MALDI-TOF MS and LC–MS/MS, with statistical analysis correlating peptide profiles with clinical outcomes like disease-free survival (DFS) and overall survival (OS). A 365-day DFS cut-off effectively distinguished early from late recurrence, with early recurrence linked to poorer survival outcomes. The PMFs from MALDI-TOF MS differentiated recurrence types based on specific mass signatures. LC–MS/MS analysis identified 95 peptides associated with cancer progression in early recurrence and 60 in late recurrence. Distinct protein associations were found: ATR, POLA1, BLM, SP100, and PPP1R15A for early recurrence, and SERPINA1, TGFB2, SERPING1, and CAD for late recurrence, with strong interactions with chemotherapeutic drugs. This study successfully demonstrated the use of PMFs for rapid discrimination between early and late recurrence in CCA and identified potential serum peptide biomarkers to improve accuracy in recurrence classification.